Localized Fournier's Gangrene in “End-Stage” Renal Failure: Multidisciplinary Approach and Integration of Palliative Care - Voordeckers, M. (Case Rep Nephrol, 2020)
Presentation of the Case. Penile gangrene is a rare entity with significant morbidity and mortality. There are only few case reports of isolated penile Fournier's gangrene in literature. Its rare occurrence, associated with complex and serious comorbidity, poses a major challenge to the attending medical personnel. A 53-year-old Caucasian patient with poorly controlled diabetes, progressive renal insufficiency, and multiple vascular complications presented with progressive necrosis of the penis (localized Fournier's gangrene). Discussion. Fournier's gangrene or necrotizing fasciitis refers to any synergistic necrotizing infection of the external genitalia or perineum and is a hallmark of severe systemic vascular disease. Fournier's gangrene is an absolute emergency because the time interval between diagnosis and treatment significantly influences morbidity and mortality. Despite aggressive management, the estimated mortality rates range from 57 to 71%. Conclusions. Improved integration of palliative care services into the care of such patients is important to improve end-of-life care even though they do not have a malignant disease. The “Palliative Care Indicator Tool” can help identifying people at risk of deteriorating health and is important to improve end-of-life care.